Anatomy of the trading process empirical evidence on the behavior of institutional traders - Keim, Donald B.; Madhavan, Ananth (Journal of Financial Economics, 1995)
This paper examines the behavior of institutional traders. We use unique data on the equity transactions of 21 institutions of differing investment styles which provide a detailed account of the anatomy of the trading process. The data include information on the number of days needed to fill an order and types of order placement strategies employed. We analyze the motivations for trade, the determinants of trade duration, and the choice of order type. The analysis provides some support for the predictions made by theoretical models, but suggests that these models fail to capture important dimensions of trading behavior.